Correlation of clinical characteristics between patients with seasonal influenza and patients infected by the wild type or delta variant of SARS-CoV-2 - Zhang, Jianguo; Huang, Xing; Tao, Zhimin (Frontiers in Public Health, 2022)
Background We compared the clinical characteristics of the patients with COVID-19, infected by the wild type or delta variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in connection with those of patients with seasonal influenza, all in mild cases. Methods We retrospectively studied 245 and 115 patients with mild COVID-19 infected by the wild type and the delta variant of SARS-CoV-2, respectively, with their demographic information, medical history, and laboratory data from hospital records, individually compared to 377 patients with mild seasonal influenza, before and after individual treatment. Results Compared to the influenza cohort, the COVID-19 cohort or the COVID-19 delta variant cohort demonstrated younger median age, lower male ratio, and shorter duration from disease onset to hospitalization. Hypertension remained the top comorbidity among all cohorts. Based on patients' data upon hospitalization, the correlation of clinical characteristics between patients with influenza and those with the wild-type COVID-19 is greater than that between patients with influenza and those with the delta variant COVID-19. Individual treatment in each viral disease alleviated most hematological parameters, but some compromised biomarkers at the time of hospital discharge revealed persistent renal or myocardial impairment among patients with COVID-19 and influenza in recovery. Conclusion Timely and proper treatment using broad-spectrum antibiotics and antiviral drugs could moderately alleviate the acute viremia and possible bacterial co-infection in patients with mild COVID-19 and influenza, followed by compromised recovery. To prepare for the flu season amid the COVID-19 pandemic, preventive and adequate immunizations of both flu and COVID-19 vaccines, as well as specific therapeutics to effectively reverse viral impairments, are in urgent need.